Market Share Factors of Sharia Banks in Indonesia and Malaysia - Gazani, Hawa; Asiyah, Binti Nur; Hidayah, Nurul (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
This research aims to examine the relationship between the market share of sharia banks in Malaysia and Indonesia simultaneously as a function of profit sharing, number of offices, and Third-Party Funds (TPF), with Return on Assets (ROA) as an intermediary variable. Both countries have similarities in being a country with a Muslim majority population and implementing a dual banking system. The annual financial reports of Sharia banks in Indonesia and Malaysia from 2016-2021 are the secondary data source for this quantitative research. A technique called path analysis is used. According to research, there is no statistically significant relationship between TPF and market share. The market share of Sharia banks is strongly influenced by profit sharing. Market share is strongly influenced by the number of offices. The impact of TPF on ROA-based market share is not significant. ROA is the main mechanism by which profit sharing affects market share. Through the ROA of Sharia banks, the number of offices influences market share. If Sharia banks want to maximize income, grow their overall assets, and increase their market share, then Sharia banks must think about how to manage TPF more effectively and efficiently, based on the conclusions of this research.